DIREITO HUMANO FUNDAMENTAL À ÁGUA POTÁVEL E AO SANEAMENTO: DA COOPERAÇÃO INTERNACIONAL À NACIONAL - ALYRE MARQUES PINTO (2023)
This Master's dissertation explores the theme of recognizing the right to drinking water and sanitation as fundamental human rights, investigating the contribution of cooperative action at both the international and national levels in realizing these rights. In the international context, joint responsibility and necessary solidarity among peoples emerge as essential for the materialization of the rights under analysis and as a means to safeguard the survival of humanity itself. In Brazil, the renewed institutional legal framework for national basic sanitation, provided by the 2020 reform, reaffirms the national federative pact and elects joint and integrated management as a favorable instrument for universalizing water supply and sanitation services. Therefore, the research problem aims to answer the following question: If cooperation mechanisms prove to be essential for the effectiveness of the fundamental human rights to drinking water and sanitation, what would be the legal basis for cooperative action by nation-states in the international context and by federative entities in the national context? To this end, the general objective is to examine the legal basis for this cooperative action by nation-states and national federative entities in the field of fundamental human rights to drinking water and sanitation. The specific objectives are as follows: i) analyze the legal configuration of the fundamental human right to drinking water and sanitation and the historical trajectory of its affirmation on the international stage; ii) assess the impacts of the global water crisis on the rights under analysis; iii) investigate the relevance of solidary international cooperation among nation-states for the effectiveness of the rights in question; iv) delimit the panorama of the fundamental right to drinking water and sanitation in Brazil; v) understand Brazilian federalism and its propensity for fostering public partnerships; vi) investigate the importance of cooperation among national federative entities for the effectiveness of the rights under analysis; and vii) analyze constitutional cooperation mechanisms favorable to shared management of public water supply and sewage services. In order to achieve these objectives and respond to the problem raised, the deductive scientific method is adopted, under a dogmatic and axiological theoretical-methodological approach and a post-positivist epistemological paradigm, with support in bibliographical and documental research, of the exploratory and qualitative type.